SEARCH FOR DIAGNOSTIC RELATIONSHIPS IN PATIENTS WITH IRRITABLE BOWEL SYNDROME AND COLORECTAL POLYPS - Kyrian, O.A. (World of Medicine and Biology, 2020)
The article describes the problems of diagnosis of irritable bowel syndrome and adenomatous colorectal polyps. The purpose of the study was to identify possible hereditary factors in the development of irritable bowel syndrome and adenomatous colorectal polyps in adults. It was found that single nucleotide polymorphisms of IL-10 wild genotype gene (rs1800871), homozygous genotype of IL-10 gene (rs1800896), heterozygous genotype of IL-1 gene (rs 16944), wild and homozygous genotypes of CHEK2 gene (rs 17879961) are associated with the development of irritable bowel syndrome. Single nucleotide polymorphisms of IL-10 wild genotype gene (rs1800896) and MMP 9 heterozygous genotype gene (rs11697325) had a significant effect for adenomatous colorectal polyps. The overall effect and relationship for patients with both diseases was determined by Tlr2 (rs 5743708), Tlr4 (rs4986790) and TgFb1 (rs 1800471) gene polymorphisms. The study results show that gene polymorphisms can affect both each disease individually, and be a unifying factor influencing the development of irritable bowel syndrome and adenomatous colorectal polyps, and also affect the general mechanisms of progression and possible neoplastic transformation on the background of functional disease.
Keywords: irritable bowel syndrome; adenomatous colorectal polyps; single nucleotide polymorphism; gene